Low baseline awareness of gastric cancer risk factors amongst at-risk multiracial/ethnic populations in New York City: results of a targeted, culturally sensitive pilot gastric cancer community outreach program. Issue 2 (17th February 2020) - Shah, Shailja C.; Nunez, Helen; Chiu, Sophia; Hazan, Ariela; Chen, Sida; Wang, Shutao; Itzkowitz, Steven; Jandorf, Lina
ABSTRACT: Background and Aims: There are limited efforts to address modifiable risk factors for gastric cancer (GC) among racial/ethnic groups at higher GC risk, which may reflect decreased public awareness of risk factors. Our primary aim was to assess baseline awareness of GC risk factors and attitudes/potential barriers for uptake of a GC screening program among high-risk individuals. Methods: Participants attended a linguistically and culturally targeted GC educational program in East Harlem (EH)/Bronx and Chinatown communities in New York City. Demographic information and relevant behavioral/lifestyle habits were collected. Participants' ability to identify GC risk factors and attitudes/barriers surrounding GC screening were assessed before and after the program. Results: Of the 168 included participants, most were female with 77% above age 70. Nearly half of participants in the EH/Bronx programs identified themselves as black and 63% as Hispanic/Latino; 93% of the Chinatown participants identified as Chinese. Among EH/Bronx participants, the majority correctly identified older age, smoking, alcohol, H. pylori, family history, race/ethnicity, excess salt, and preserved foods as risk factors. Among Chinatown participants, the majority correctly identified smoking, alcohol, race/ethnicity, and excess salt, although only 53% and 57.8% correctly identified H. pylori and preserved foods, respectively; the majority incorrectly answered that older age was not a major risk factor. The majority in both groups failed to identify male gender as higher risk and incorrectly identified stress and obesity as major risk factors. Participants were more concerned about the potential findings on GC screening tests than the risks and costs or having to take time off work. Conclusion: Among multiracial/ethnic groups of individuals presumably at higher risk for GC, we identified several gaps in baseline knowledge of both modifiable and non-modifiable GC risk factors. Culturally and linguistically appropriate educational interventions may be a worthwhile adjunctive intervention within the context of a targeted GC screening program.